SIKAP DAN STIGMA PERAWATAN JIWA PADA PASIEN SKIZOFRENIA DI RSJ PROF. HB SAANIN - Nugroho, Nehru (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
Schizophrenic patients experience limitations to perform their role as normalhumans. This limitation makes the beliefs of nurses form perceived attributes deviate aspeople with mental disorders that are difficult to cure, unpredictable and discriminatoryoccurrence known as stigmatization. The aim of this research was to identify the relationshipbetween attitudes with the stigma of mental nurses in schizophrenic patients. Descriptiveanalytic research design, cross sectional approach. A sample of 140 nurses, makingthe entire population a subject of research. The result of the research was the attitudeof the nurse's authority to show the negative attitude, the attitude of the virtue, the socialrestriction and the ideology of mental health community showed positive nurse attitude.Most stigma of nurses in schizophrenic patients was high. There was a relationship betweensocial restriction and nurse stigma in schizophrenic patients. While there is no correlationbetween attitude of authority, virtue, and ideology of mental health communitywith stigma of nurse in schizophrenic patient at RSJ Prof.HB Saanin Padang 2015. Suggestionfor institution especially in nursing field conducting education and training onnurse about stigma of nurse in schizophrenia patient so nurse able to reduce the occurrenceof stigma especially discrimination by nurse and patient get more optimal nursingservice.